Ansiedad y su influencia en el entorno familiar de un paciente de la Unidad de Hemodiálisis Dialrios del cantón Vinces - Laje Litardo, Selena del Rocío (2020)
The study has the objective of Analyzing how anxiety influences the family environment of a patient with catastrophic disease through the case study, to evaluate techniques for the study such as observation, interview, clinical history and the Scale Test were used of Hamilton anxiety, where it was found that the patient manifests The patient presents feelings of fear, worry, irritability, pessimism, feeling of fatigue, sweating in the hands, physical tension, difficulty in falling asleep and sweating in the hands, resulting in A generalized anxiety disorder, this actively affects the family system and in turn displaces feelings of loneliness, suicidal ideas, difficulty in showing their emotions, which causes the family system to deteriorate according to the severity of the patient's problem. As a proposal, a psychotherapeutic plan will be given through passive relaxation therapy, through the course of 4 sessions, to reduce anxiety levels to be able to bring about any situation and create an adequate environment for the proper use of activities other than those that are Get used to it, taking into account their time for classes and homework.